chứng minh 5^ ( n+3) – 3^(n+3) +5^(n+2)- 3^(n+1) chia hết cho 60
b, cho C = 1/4 + 2/4^2 + 3/4^3 +…….. +2017/4^2017
chúng ming rằng C < 1/2
giúp mk vs ạ
chứng minh 5^ ( n+3) – 3^(n+3) +5^(n+2)- 3^(n+1) chia hết cho 60
b, cho C = 1/4 + 2/4^2 + 3/4^3 +…….. +2017/4^2017
chúng ming rằng C < 1/2
giúp mk vs ạ
Giải thích các bước giải:
a.Ta có:
$A=5^{n+3}-3^{n+3}+5^{n+2}-3^{n+1}$
$\to A=(5^{n+3}+5^{n+2})-(3^{n+3}+3^{n+1})$
$\to A=5^{n+2}(5+1)-3^{n+1}(3^2+1)$
$\to A=5^{n+2}\cdot 6-3^{n+1}\cdot 10$
$\to A=5^{n+1}\cdot 5\cdot 6-3^{n}\cdot 3\cdot 10$
$\to A=5^{n+1}\cdot 30-3^{n}\cdot 30$
$\to A=30(5^{n+1}-3^{n})$
Mà $5^{n+1},3^{n}$ lẻ
$\to 5^{n+1}-3^{n}$ chẵn
$\to 5^{n+1}-3^{n}\quad\vdots\quad 2$
$\to 30(5^{n+1}-3^{n})\quad\vdots\quad 60$
$\to A\quad\vdots\quad 60$
b.Ta có:
$C=\dfrac14+\dfrac2{4^2}+\dfrac3{4^3}+…+\dfrac{2017}{4^{2017}}$
$\to 4C=1+\dfrac2{4}+\dfrac3{4^2}+…+\dfrac{2017}{4^{2016}}$
$\to 4C-C=1+\dfrac14+\dfrac1{4^2}+…+\dfrac{1}{4^{2016}}-\dfrac{2017}{4^{2017}}$
$\to 3C=1+\dfrac14+\dfrac1{4^2}+…+\dfrac{1}{4^{2016}}-\dfrac{2017}{4^{2017}}$
Mà $B=1+\dfrac14+\dfrac1{4^2}+…+\dfrac{1}{4^{2016}}$
$\to 4B=4+1+\dfrac14+…+\dfrac1{4^{2015}}$
$\to 4B-B=4-\dfrac{1}{4^{2016}}$
$\to 3B=4-\dfrac{1}{4^{2016}}$
$\to B=\dfrac43-\dfrac{1}{3\cdot 4^{2016}}$
$\to 3C=(1+\dfrac14+\dfrac1{4^2}+…+\dfrac{1}{4^{2016}})-\dfrac{2017}{4^{2017}}$
$\to 3C=B-\dfrac{2017}{4^{2017}}$
$\to 3C=\dfrac43-\dfrac{1}{3\cdot 4^{2016}}-\dfrac{2017}{4^{2017}}$
$\to 3C<\dfrac43$
$\to C<\dfrac49<\dfrac48=\dfrac12$